Kafka for the twenty-first century - Corngold, Stanley; Gross, Ruth von (Camden House, 2011)
Running texts, stunning drafts / Roland Reuss -- "Torturing the Gordian Knot" : Kafka and Metaphor / Mark Harman -- Nietzsche and Kafka : the Dionysian connection / Walter H. Sokel -- What Kafka learned from Flaubert : "Absent-minded window-gazing" and "The judgment" / Uta Degner -- Kafka's racial melancholy / Katja Garloff -- Strange loops and the absent center in The castle / Jacob Burnett -- Proxies in Kafka : Koncipist FK and Prokurist Josef K. / Doreen Densky -- Kafka, Goffman, and the total institution / Ritchie Robertson -- Kafka in Virilio's Teletopical city / Rolf J. Goebel -- Kafka's visual method : the gaze, the cinematic, and the intermedial / Peter Beicken -- "Samsa war Reisender" : trains, trauma, and the unreadable body / John Zilcosky
Hier auch später erschienene, unveränderte Nachdrucke
Hier auch später erschienene, unveränderte Nachdrucke
Keywords: Kafka, Franz -- 1883-1924 -- Criticism and interpretation; Aufsatzsammlung; Konferenzschrift; Kafka, Franz